Design and scale-up of continuous di-nitration reaction using pinched tube flow reactor - Hussain, Arshad; Sharma, Mrityunjay; Patil, Suneha; Acharya, Roopashree B.; Kute, Mahesh; Waghchaure, Aishwarya; Kulkarni, Amol A. (Journal of Flow Chemistry, 2021)
Scale-up of the di-nitration reaction for synthesis of selective herbicide pendimethalin using only nitric acid in continuous flow is presented in this work. This work showcases an approach for smooth scale-up for an herbicide for a production capacity of 50 kg/day using a pinched tube reactor. The approach begins with the batch experiments followed by flow synthesis using a 1/8-inchSS316 helical coil tube where kinetics of the di-nitration was determined, and process optimization was done. Systematic approach was followed for quantification of heat transfer, mass transfer and residence time distribution and scale-up. Detailed scale-up methodology is presented with effect of relevant parameters for successful scale-up. Modular pilot plant with inline quenching, extraction and separation are some of the salient features presented in this work.
Keywords: continuous flow; nitration; Pinched tube; RTD; scale-up

Inkjet printing of silver nanowires on flexible surfaces and methodologies to improve the conductivity and stability of the printed patterns - Patil, Prathamesh; Patil, Suneha; Kate, Prachi; Kulkarni, Amol A. (Nanoscale Advances, 2021)
Silver nanowires (AgNWs) are known to be used for printing on rigid as well as flexible surfaces. Here we have developed a systematic approach for using AgNWs synthesized by the polyol method for printing on flexible surfaces using a simple inkjet printing method. Optimized ink formulation used in this work comprises a mixture of Ag NWs suspended in ethylene glycol directly taken after synthesis and isopropyl alcohol. Using such formulation saves time and loss of material while transferring to other solvents, which is the usual practice. The printed patterns demonstrate high conductivity and stability over many months, which can revolutionize the applications of functional nanomaterials in low-cost printed electronics. The importance of fragmentation of nanowires only to achieve specific aspect ratios, to facilitate easy jetting and to prevent clogging is demonstrated. Varied concentrations (10 mg mL(-1) to 50 mg mL(-1)) of Ag NWs are used in ink formulations in order to print highly conductive patterns (resistance < 50 Omega sq(-1)) in a minimal number of passes. The same composition was also seen to facilitate simple and time-efficient nano-welding at room temperature, which improves the conductivity and stability of the printed patterns.

Quantitative understanding of nucleation and growth kinetics of silver nanowires - Patil, Suneha; Kate, Prachi R.; Deshpande, Jaydeep B.; Kulkarni, Amol A. (Chemical Engineering Journal, 2021)
We have demonstrated that using polyol synthesis, it is possible to prepare high aspect ratio silver nanowires by controlling the experiments for process related issues which are usually ignored, viz. the overhead space in the batch reactor. It is found that by controlling the presence/absence of NOx gases with refluxing of nitric acid in the batch reactor with an overhead space of 80% volume, near complete conversion (-99%) of high aspect ratio NWs (-1000) can be attained. We provide a detailed understanding of other factors assisting in rapid polyol synthesis like temperature, stirring rate, Chloride ion concentration, optimal PVP weight ratios and PVP/AgNO3 ratio that can lead to high aspect ratio NWs. Besides the process parameters and reagent concentration effects, kinetic studies based on our nucleation and R-C Model evaluate the overall reaction rate constants for silver nanowires and the JMAK approach is used to theoretically validate our experimental results of the reactor headspace having strongest effect on the aspect ratios. Our study highlights the importance of various complications in the polyol synthesis, through detailed kinetic modelling and affixes values of temperature, reactor headspace, stirring rate and residence time in order to achieve reproducible synthesis of nanowires with complete conversion along with a method to separate these nanowires.
Keywords: Conducting inks; growth; Nucleation; Reaction kinetics; Redox-crystallization; Silver Nanowires

Direct (hetero)arylation (DHAP) polymerization of conjugated polymers - new A-B-A monomer design for P(NDI2OD-T2) & the challenges of adopting DHAP for continuous flow processes - Kakde, Navnath R.; Bharathkumar, H. J.; Wavhal, Bhaiyyasaheb A.; Nikam, Arun; Patil, Suneha; Dash, Soumya Ranjan; Vanka, Kumar; Krishnamoorthy, K.; Kulkarni, Amol; Asha, S. K. (Journal of Materials Chemistry C, 2022)
P(NDI2OD-T2), also known as Polyera ActivInk N2200, was synthesized by the atom-economic direct hetero arylation polymerization (DHAP) route using a newly designed A-B-A monomer. The new monomer design involved flanking naphthalene diimide with bithiophene units in the bay position, which was further polymerized with bay substituted 1,4-dibromo naphthalene diimide, to afford the same polymer structure as P(NDI2OD-T2). The new monomer design resulted in a very high molecular weight (M-n: 99.5 kDa, D-M: 2.8) defect-free polymer in a quantitative yield by the DHAP batch process using 1,2,4-trichlorobenzene (TCB) as the solvent. DFT studies revealed that the abstraction of the alpha-proton from the naphthalene diimide substituted 2,2 `-bithiophene was favorable by 2.6 kcal mol(-1) (Delta Delta G) as compared to that from 2,2 `-bithiophene. The reason for this improved C-H activation at the alpha position can be attributed to the presence of C-HMIDLINE HORIZONTAL ELLIPSIS pi stabilizing interactions in naphthalene diimide substituted 2,2 `-bithiophene, which strengthens upon the extended charge delocalization throughout the ring, thus stabilizing the conjugate base generated after the proton abstraction. Continuous flow polymerization was carried out by pumping the DHAP reaction mixture including the monomers, catalyst, and additive (pivalic acid) solubilized in degassed TCB through a pre-heated glass condenser packed with K2CO3 and Celite under aerobic conditions. Reproducible molecular weights of M-n: 29.5 kDa, D-M: 1.7 were obtained at much lower concentrations of reactant mixture compared to that for batch polymerization. This is the first report of the synthesis of P(NDI2OD-T2) by a Continuous Flow Process adopting the DHAP route to obtain a defect-free polymer with reasonable molecular weights. P(NDI2OD-T2) was also synthesized by Stille polymerization as a reference control sample to compare the thermal and charge carrier transport properties of the DHAP polymers. Organic field-effect (OFET) mobility measurements indicated mobility values in the order of 10(-3) cm(2) V-1 s(-1) for the DHAP batch polymer (using the novel monomer design). The P(NDI2OD-T2) synthesized by DHAP batch using the commonly used starting materials - bisbromo naphthalene diimide and bithiophene, exhibited OFET mobilities which were one order less, similar to 10(-4) cm(2) V-1 s(-1). This observation highlights the importance of structural design in the monomer to enhance reactivity and thereby the bulk properties using the DHAP route.

Understanding the nucleation and growth kinetics of the microwave-assisted synthesis of silver nanowires - Sonawane, Jayesh R.; Patil, Suneha; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2023)
Here, we present a detailed study of understanding the nucleation and growth kinetics of silver nanowire synthesis under microwave irradiation. The approach includes studying the effect of various parameters (viz., microwave power, reaction temperature, reaction time, substrate concentration, etc.) on the rate of nucleation and growth, as well as on the yield and morphology of silver nanowires. It is found that microwave power is the most important factor in leading to almost complete conversion of the substrate along with high aspect ratio nanowires in a short reaction time. Based on the observations, here, we have proposed a three-step growth kinetics mechanism for the synthesis of silver nanowires under the influence of microwaves. The approach comprises the autocatalytic growth of stable multiple twin particles after the nucleation process and their unidirectional growth to form nanowires. The FW autocatalytic model and the JMAK Avrami model were used to validate the proposed mechanism of AgNW formation based on our experimental results. The model predictions match very well with the conversion and yield of AgNWs. At the optimized conditions, wires with a 42 nm diameter and 94% yield were achieved within 4 min.